2019
DOI: 10.1002/elps.201900295
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics comparison of exosomes from serum and plasma between ultracentrifugation and polymer‐based precipitation kit methods

Abstract: Exosomes are vesicles with sizes ranging from 30 to 150 nm. The analysis and detection of blood exosomes offers an effective route for cancer diagnosis, prognosis assessment, and therapeutic evaluation of diseases. Due to the difference in separation procedure, collection method and the usage of anticoagulants, serum and plasma samples show diversity test results. In order to evaluate the isolation effect of exosomes in serum and plasma samples, two commonly used exosomal isolation methods, ultracentrifugation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 36 publications
1
38
0
Order By: Relevance
“…145 Furthermore, there is still a debate whether plasma or serum is a better source of sEVs for clinical applications. Though plasma sEVs are deemed to contain more sEVs biomarkers and better for diagnosis than serum sEVs, 146 plasma contains platelets that are able to release several types of membrane vesicles, 147 which will confound the measurement of circulating miRNA biomarkers in plasma, 148,149 and even more nonvesicle miRNAs. 150 Nevertheless, compared to plasma, sEVs originated miRNAs are more highly expressed in serum sEVs samples.…”
Section: Discussionmentioning
confidence: 99%
“…145 Furthermore, there is still a debate whether plasma or serum is a better source of sEVs for clinical applications. Though plasma sEVs are deemed to contain more sEVs biomarkers and better for diagnosis than serum sEVs, 146 plasma contains platelets that are able to release several types of membrane vesicles, 147 which will confound the measurement of circulating miRNA biomarkers in plasma, 148,149 and even more nonvesicle miRNAs. 150 Nevertheless, compared to plasma, sEVs originated miRNAs are more highly expressed in serum sEVs samples.…”
Section: Discussionmentioning
confidence: 99%
“…However, our study results demonstrated that DGUC and IAC methods produced sEVs with better purity than UC. Besides, the interpretation of results should be cautious when commercial sEVs isolation kits based on the Co-P method was used 38,45 . The combination of several isolation methods may produce purer sEVs.…”
Section: Discussionmentioning
confidence: 99%
“…To facilitate the clinical application of exosomes, efficient separation and storage methods are essential. The current methods for isolating exosomes primarily comprise ultracentrifugation (Baranyai et al, 2015), the microfluidic chip method (Zhang et al, 2019), the antibody affinity capture method (Mathivanan et al, 2010), the polymer precipitation method (Cao F. et al, 2019), and gel exclusion chromatography (Hayashi et al, 2019). Of these, the most commonly used method is ultracentrifugation.…”
Section: Exosome Isolation and Storagementioning
confidence: 99%